Swedish agriculture under reorganization - Conditions and strategies of farming households 1992 - Djurfeldt, Göran; Nitsch, Ulrich; Waldenström, Cecilia (Lund University, 1998)
This is a survey of farming households in three different areas of Sweden. Swedish agriculture is presently undergoing a radical reorganization. Regulation systems are dismantled and free markets are established. The technical development, as well as the environmental problems, makes the future uncertain. The reorganization of agriculture brings about big changes for the individual farmer, and their work and living conditions are changed considerably. The project was financed by the Swedish Council for Forestry and Agricultural Research, the Swedish Council for Building Research, the Swedish Work and Environment Fund and the Swedish Farmers´ Foundation for Agricultural Research.

This is a survey of farming households in three different areas of Sweden. Swedish agriculture is presently undergoing a radical reorganization. Regulation systems are dismantled and free markets are established. The technical development, as well as the environmental problems, makes the future uncertain. The reorganization of agriculture brings about big changes for the individual farmer, and their work and living conditions are changed considerably. The project was financed by the Swedish Council for Forestry and Agricultural Research, the Swedish Council for Building Research, the Swedish Work and Environment Fund and the Swedish Farmers´ Foundation for Agricultural Research.
Svenskt lantbruk under omställning - lantbrukshushållens villkor och strategier 1992
Keywords: economics; ekonomi; leisure time; fritid; environmental degradation; miljöförstörelse; child care; barnomsorg; local government services; kommunal service; membership; medlemskap; income; inkomst; farmers; jordbrukare; educational background; utbildningsbakgrund; employment history; anställningshistorik; agricultural enterprises; jordbruksföretag; forestry; skogsbruk; ecology; ekologi; pesticides; bekämpningsmedel; agricultural products; jordbruksprodukter; farms; bondgårdar; crops; grödor; animal breeding; djuruppfödning; households; hushåll; leisure time activities; fritidsaktiviteter; social activities (leisure); sociala aktiviteter (fritid); organizations; organisationer; rural economics; landsbygdsekonomi; area measurement; ytmått; agriculture; lantbruk; farming; jordbruk; hours of work; arbetstid; agricultural production; jordbruksproduktion; Employment; Sysselsättning; Working conditions; Arbetsförhållanden; Gender and gender roles; Kön och könsroller; Community, urban and rural life; Lokalsamhälle, stads- och landsbygdsliv; Agriculture and rural industry; Jordbruk och landsbygdsnäring; Social Sciences; Samhällsvetenskap; Sociology; Sociologi